Self-compacting polymer concrete for repairing and preparation method thereof

By using porous sintered sand, quartz sand, wood fibers and modified aggregates in polymer concrete, the problems of inconvenience in construction, large shrinkage and insufficient strength are solved, and high strength, low shrinkage and strong bonding are achieved. Improves repair effect and service life.

CN119191810APending Publication Date: 2024-12-27BEIJING EONZEAL WATERPROOF MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411454212.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-17
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

During the repair process, existing polymer concrete often encounters problems such as inconvenient construction, large shrinkage, insufficient strength and poor adhesion, resulting in poor repair effect and short service life.

Method used

By using a self-solidified polymer concrete for repair, including cement, porous sintered sand, quartz sand, gypsum, aggregate, wood fiber, water-retaining polymer, expansion agent and water-reducing agent, the quality of porous sintered sand and wood fibers is controlled. The ratio and particle size are used to modify the aggregate with a compound containing naphthalene ring and carboxyl group, combined with an appropriate amount of expansion agent and water reducing agent to enhance the compressive strength and flexural strength of the concrete, and improve the combination of porous sintered sand and wood fibers. Water absorption and water retention ability reduces the risk of shrinkage.

Benefits of technology

It realizes convenient construction without mechanical vibration, avoids the shrinkage of traditional concrete, improves the strength and durability of concrete, enhances bonding and anti-corrosion properties, reduces the risk of cracking, and extends the service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention relates to the technical field of building materials, and provides self-compacting polymer concrete for repairing and a preparation method thereof. The self-compacting polymer concrete for repairing is prepared from the following components in parts by mass: 15 to 35 parts of cement, 10 to 20 parts of porous sintered sand, 10 to 20 parts of quartz sand, 5 to 10 parts of gypsum, 25 to 35 parts of aggregate, 0.2 to 1.5 parts of wood fiber, 0.5 to 3 parts of water-retaining polymer, 1 to 3 parts of expanding agent, 0.3 to 1 part of water reducing agent and 0.05 to 0.3 part of early strength agent. According to the technical scheme, the problems of high shrinkage, low strength and poor cohesiveness of polymer concrete in the related technology are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building materials, and in particular to a self-compacting polymer concrete for repair and a preparation method thereof. Background Art

[0002] Polymer concrete refers to concrete made of organic polymers, inorganic cementitious materials and aggregates. The introduction of organic polymers has the effects of toughening, plasticizing, filling pores and solidifying concrete, which to a certain extent solves the shortcomings of ordinary concrete, such as high brittleness and easy cracking, and greatly broadens the application field of concrete. It is often used for on-site pouring of structures, road surfaces and bridge deck repairs.

[0003] At present, polymer concrete on the market often encounters problems such as inconvenient construction, large shrinkage, insufficient strength, and poor adhesion during the repair process, resulting in poor repair effects and short service life. Summary of the invention

[0004] The invention provides a self-compacting polymer concrete for repair and a preparation method thereof, which solves the problems of large shrinkage, low strength and poor adhesion of polymer concrete in the related art.

[0005] The technical solution of the present invention is as follows: A self-compacting polymer concrete for repair comprises the following components in parts by weight: 15-35 parts of cement, 10-20 parts of porous sintered sand, 10-20 parts of quartz sand, 5-10 parts of gypsum, 25-35 parts of aggregate, 0.2-1.5 parts of wood fiber, 0.5-3 parts of water-retaining polymer, 1-3 parts of expansion agent, 0.3-1 parts of water reducing agent and 0.05-0.3 parts of early strength agent.

[0006] As a further technical solution, the mass ratio of the porous sintered sand to the wood fiber is 20:1.

[0007] The present invention controls the mass ratio of porous sintered sand to wood fiber to be 20:1, thereby further improving the compressive strength and flexural strength of the polymer concrete.

[0008] As a further technical solution, the particle size of the porous sintered sand is 0.3~1.2mm.

[0009] As a further technical solution, the particle size of the quartz sand is 0.5~1.0mm.

[0010] As a further technical solution, the length of the wood fiber is 0.5-3 mm and the diameter is 20-300 μm.

[0011] As a further technical solution, the expansion agent includes one or both of a magnesium oxide expansion agent and a calcium sulfoaluminate expansion agent.

[0012] As a further technical solution, the water reducer includes a polycarboxylate water reducer.

[0013] As a further technical solution, the aggregate includes a first aggregate and a second aggregate in a mass ratio of 1:10 to 10:1, the first aggregate is an unmodified aggregate, and the second aggregate is an aggregate modified by a compound containing a naphthalene ring and a carboxyl group.

[0014] The present invention uses unmodified aggregate and aggregate modified by a compound containing a naphthalene ring and a carboxyl group in a mass ratio of 1:10 to 10:1, thereby further improving the compressive strength and flexural strength of the polymer concrete. After part of the aggregate is modified by the compound containing a naphthalene ring and a carboxyl group, the carboxyl group forms a hydrogen bond with the hydroxyl group on the surface of the aggregate, thereby being adsorbed on the surface of the aggregate. Then, the combination between the inorganic aggregate and the polymer can be promoted by using the unmodified aggregate in combination, thereby achieving the effect of improving the strength.

[0015] The compound containing a naphthalene ring and a carboxyl group in the present invention may be any compound containing a naphthalene ring and a carboxyl group, for example, it may be one or more of 1-naphthalenecarboxylic acid, 2-naphthalenecarboxylic acid, and 1,4-naphthalenedicarboxylic acid, preferably 1,4-naphthalenedicarboxylic acid.

[0016] As a further technical solution, the mass ratio of the first aggregate to the second aggregate is 3-4:1.

[0017] The present invention limits the mass ratio of the first aggregate to the second aggregate to 3-4:1, thereby further improving the compressive strength and flexural strength of the polymer concrete.

[0018] As a further technical solution, the raw materials of the second aggregate include a compound containing a naphthalene ring and a carboxyl group and aggregate in a mass ratio of 1 to 5:50.

[0019] As a further technical solution, the preparation method of the second aggregate comprises the following steps: dissolving a compound containing a naphthalene ring and a carboxyl group in a solvent, adding the compound into the aggregate and mixing the mixture evenly, and drying the mixture to obtain the second aggregate.

[0020] As a further technical solution, the gypsum includes one or both of anhydrous gypsum and hemihydrate gypsum.

[0021] As a further technical solution, the aggregate includes one or two of limestone crushed stones and pebbles.

[0022] As a further technical solution, the water-retaining polymer includes one or both of polyvinyl alcohol and sodium polyacrylate; the early strength agent includes one or both of triethanolamine and diethanolamine.

[0023] The invention also provides a method for preparing the self-compacting polymer concrete for repair, which comprises uniformly mixing the components in parts by mass to obtain the self-compacting polymer concrete for repair.

[0024] The working principle and beneficial effects of the present invention are: The polymer concrete provided by the present invention has the following advantages: 1. It does not require mechanical vibration and can be constructed by manual vibration or even without vibration, which is convenient for construction and can be self-compacted and has good self-compactness; 2. It avoids the shrinkage phenomenon of traditional concrete during hydration and hardening and has no shrinkage; 3. It has the ability to maintain the interior of concrete, which can improve the strength grade of concrete and improve the working performance during construction. Due to the coordinated use of porous sintered sand and wood fiber, the concrete has excellent water absorption and water retention capabilities. During the mixing process, they will absorb part of the free water, and during the concrete hardening process, they can slowly release the water, which can provide the necessary water for the hydration reaction of cement over a long period of time. The "internal curing" effect helps cement to hydrate more fully, thereby improving the strength and durability of concrete; by adjusting the free water content in concrete, porous sintered sand and wood fiber can maintain the workability of concrete within a wider range, which means that concrete can maintain good working performance during mixing, transportation and pouring, thereby improving construction performance; the water retention properties of porous sintered sand and wood fiber also help reduce the plastic shrinkage and drying shrinkage of concrete, thereby reducing the risk of cracking and improving crack resistance; ④ The bonding performance between new and old concrete is strong, and there is no need to apply interface treatment agent, with strong bonding; ⑤ It effectively prevents steel bar corrosion, improves structural durability, and has good anti-corrosion performance. DETAILED DESCRIPTION

[0025] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0026] The parameters of the raw materials in the following examples and comparative examples are as follows: The cement is 42.5 grade ordinary Portland cement; The polyvinyl alcohol is polyvinyl alcohol 2488; The polycarboxylate water reducer is polycarboxylate water reducer 530P; The particle size of quartz sand is 20 mesh; The gradation of limestone crushed stone and pebbles conforms to the continuous gradation of 0.5~2.5cm; The bulk density of wood fiber is 0.35~0.4g / cm 3, length 0.5~3mm, diameter 20~300μm; Sodium polyacrylate is sodium polyacrylate NP-700; The porous sintered sand is prepared by the following method: 70 parts of natural sand, 25 parts of clay, 8 parts of albite, 0.8 parts of sodium carboxymethyl cellulose, and 8 parts of calcium carbonate are mixed, 40 parts of water are added and the mixture is mixed until uniform, ball-milled to less than 200 mesh, spray-dried to prepare 1.0 mm particles, transferred to a kiln, sintered at 1100°C for 4 hours, and cooled to obtain the porous sintered sand.

[0027] Example 1 25 parts of cement, 18.7 parts of porous sintered sand, 15 parts of quartz sand, 5 parts of hemihydrate gypsum, 33 parts of limestone gravel, 0.2 parts of wood fiber, 0.5 parts of polyvinyl alcohol, 2 parts of magnesium oxide expansion agent, 0.5 parts of polycarboxylate water reducer and 0.1 parts of triethanolamine are mixed and stirred evenly, and bagged to obtain self-compacting polymer concrete for repair.

[0028] Example 2 15 parts of cement, 10 parts of porous sintered sand, 10 parts of quartz sand, 8 parts of anhydrous gypsum, 25 parts of pebbles, 0.2 parts of wood fiber, 1.5 parts of sodium polyacrylate, 1 part of calcium sulfoaluminate expansion agent, 0.3 parts of polycarboxylate water reducer and 0.05 parts of diethanolamine are mixed and stirred evenly, and bagged to obtain self-compacting polymer concrete for repair.

[0029] Example 3 35 parts of cement, 20 parts of porous sintered sand, 20 parts of quartz sand, 10 parts of hemihydrate gypsum, 35 parts of pebbles, 0.2 parts of wood fiber, 3 parts of sodium polyacrylate, 3 parts of calcium sulfoaluminate expansion agent, 1 part of polycarboxylate water reducer, and 0.3 parts of triethanolamine are mixed and stirred evenly, and bagged to obtain self-compacting polymer concrete for repair.

[0030] Example 4 25 parts of cement, 18 parts of porous sintered sand, 15 parts of quartz sand, 5 parts of hemihydrate gypsum, 33 parts of limestone crushed stone, 0.9 parts of wood fiber, 0.5 parts of polyvinyl alcohol, 2 parts of magnesium oxide expansion agent, 0.5 parts of polycarboxylate water reducer and 0.1 parts of triethanolamine were mixed and stirred evenly, and bagged to obtain self-compacting polymer concrete for repair.

[0031] Example 5 25 parts of cement, 17.4 parts of porous sintered sand, 15 parts of quartz sand, 5 parts of hemihydrate gypsum, 33 parts of limestone gravel, 1.5 parts of wood fiber, 0.5 parts of polyvinyl alcohol, 2 parts of magnesium oxide expansion agent, 0.5 parts of polycarboxylate water reducer and 0.1 parts of triethanolamine were mixed and stirred evenly, and bagged to obtain self-compacting polymer concrete for repair.

[0032] Example 6 S1, dissolving 5 parts of 1,4-naphthalene dicarboxylic acid in 500 parts of ethanol, adding 50 parts of limestone gravel and mixing evenly, filtering, and drying to obtain modified limestone gravel; S2. Mix 25 parts of cement, 18 parts of porous sintered sand, 15 parts of quartz sand, 5 parts of hemihydrate gypsum, 33 parts of modified limestone gravel, 0.9 parts of wood fiber, 0.5 parts of polyvinyl alcohol, 2 parts of magnesium oxide expansion agent, 0.5 parts of polycarboxylate water reducer and 0.1 parts of triethanolamine, stir well and bag them to obtain self-compacting polymer concrete for repair.

[0033] Example 7 S1, dissolving 5 parts of 1,4-naphthalene dicarboxylic acid in 500 parts of ethanol, adding 50 parts of limestone gravel and mixing evenly, filtering, and drying to obtain modified limestone gravel; S2. Mix 25 parts of cement, 18 parts of porous sintered sand, 15 parts of quartz sand, 5 parts of hemihydrate gypsum, 3 parts of limestone gravel, 30 parts of modified limestone gravel, 0.9 parts of wood fiber, 0.5 parts of polyvinyl alcohol, 2 parts of magnesium oxide expansion agent, 0.5 parts of polycarboxylate water reducer and 0.1 parts of triethanolamine, stir well, and bag to obtain self-compacting polymer concrete for repair.

[0034] Example 8 S1, dissolving 5 parts of 1,4-naphthalene dicarboxylic acid in 500 parts of ethanol, adding 50 parts of limestone gravel and mixing evenly, filtering, and drying to obtain modified limestone gravel; S2. Mix 25 parts of cement, 18 parts of porous sintered sand, 15 parts of quartz sand, 5 parts of hemihydrate gypsum, 24.75 parts of limestone gravel, 8.25 parts of modified limestone gravel, 0.9 parts of wood fiber, 0.5 parts of polyvinyl alcohol, 2 parts of magnesium oxide expansion agent, 0.5 parts of polycarboxylate water reducer and 0.1 parts of triethanolamine, stir well, and bag to obtain self-compacting polymer concrete for repair.

[0035] Example 9 S1, dissolving 5 parts of 1,4-naphthalene dicarboxylic acid in 500 parts of ethanol, adding 50 parts of limestone gravel and mixing evenly, filtering, and drying to obtain modified limestone gravel; S2. Mix 25 parts of cement, 18 parts of porous sintered sand, 15 parts of quartz sand, 5 parts of hemihydrate gypsum, 26.4 parts of limestone crushed stone, 6.6 parts of modified limestone crushed stone, 0.9 parts of wood fiber, 0.5 parts of polyvinyl alcohol, 2 parts of magnesium oxide expansion agent, 0.5 parts of polycarboxylate water reducer and 0.1 parts of triethanolamine, stir well, and bag to obtain self-compacting polymer concrete for repair.

[0036] Example 10 S1, dissolving 5 parts of 1,4-naphthalene dicarboxylic acid in 500 parts of ethanol, adding 50 parts of limestone gravel and mixing evenly, filtering, and drying to obtain modified limestone gravel; S2. Mix 25 parts of cement, 18 parts of porous sintered sand, 15 parts of quartz sand, 5 parts of hemihydrate gypsum, 30 parts of limestone gravel, 3 parts of modified limestone gravel, 0.9 parts of wood fiber, 0.5 parts of polyvinyl alcohol, 2 parts of magnesium oxide expansion agent, 0.5 parts of polycarboxylate water reducer, and 0.1 parts of triethanolamine, stir well, and bag to obtain self-compacting polymer concrete for repair.

[0037] Comparative Example 1 25 parts of cement, 18.9 parts of porous sintered sand, 15 parts of quartz sand, 5 parts of hemihydrate gypsum, 33 parts of limestone gravel, 0.5 parts of polyvinyl alcohol, 2 parts of magnesium oxide expansion agent, 0.5 parts of polycarboxylate water reducer and 0.1 parts of triethanolamine were mixed and stirred evenly, and bagged to obtain self-compacting polymer concrete for repair.

[0038] Comparative Example 2 25 parts of cement, 15 parts of quartz sand, 5 parts of hemihydrate gypsum, 33 parts of limestone gravel, 18.9 parts of wood fiber, 0.5 parts of polyvinyl alcohol, 2 parts of magnesium oxide expansion agent, 0.5 parts of polycarboxylate water reducer and 0.1 parts of triethanolamine were mixed and stirred evenly, and bagged to obtain self-compacting polymer concrete for repair.

[0039] The self-compacting polymer concrete for repair obtained in Example 4 and Comparative Examples 1-2 was mixed with water at a mass ratio of 100:20, and then cured in a standard curing room according to the method in GB / T 50081-2019 to test the 28d compressive strength, 28d flexural strength and bonding strength; and the 28d shrinkage rate was calculated by the following formula: 28d shrinkage rate (%) = (length of original specimen - length of 28d specimen) ÷ length of original specimen × 100 The results are recorded in Table 1.

[0040] Table 1 Properties of self-compacting polymer concrete for repair

[0041] It can be seen from Table 1 that the self-compacting polymer concrete for repair provided by Example 4 of the present invention has a 28d compressive strength of 55 MPa, a 28d flexural strength of 7.5 MPa, a 28d shrinkage rate of 0.015%, and a bonding strength of 2.30 MPa, and has the advantages of high strength, small shrinkage, and good adhesion.

[0042] Compared with Comparative Examples 1-2, in Example 4, the porous sintered sand and wood fiber are used in combination, and the 28d compressive strength, 28d flexural strength and bonding strength of the self-compacting polymer concrete for repair obtained are higher than those of Comparative Examples 1-2, and the 28d shrinkage rate is lower than that of Comparative Examples 1-2, indicating that the use of porous sintered sand and wood fiber in combination can improve the strength and adhesion of the self-compacting polymer concrete for repair, while reducing the shrinkage rate.

[0043] The self-compacting polymer concrete for repair obtained in Examples 1 to 10: water were mixed evenly in a mass ratio of 100:35, and then cured in a standard curing room according to the method in GB / T 50081-2019, and the 28d compressive strength and 28d flexural strength were tested. The test results are recorded in Table 2.

[0044] Table 2 Strength of self-compacting polymer concrete for repair

[0045] It can be seen from Table 2 that the self-compacting polymer concrete for repair provided by the present invention has a 28d compressive strength of more than 52.6 MPa and a 28d flexural strength of more than 6.7 MPa, and has high strength.

[0046] The 28d compressive strength and 28d flexural strength of the self-compacting polymer concrete for repair obtained in Example 4 are higher than those in Example 1 and Example 5, indicating that when the mass ratio of porous sintered sand to wood fiber is 20:1, the compressive strength and flexural strength of the polymer concrete can be further improved.

[0047] The 28d compressive strength and 28d flexural strength of the self-compacting polymer concrete for repair obtained in Examples 7 to 10 are higher than those in Examples 4 and 6, indicating that the use of unmodified aggregates and aggregates modified with compounds containing naphthalene rings and carboxyl groups can further improve the compressive strength and flexural strength of the polymer concrete.

[0048] The 28d compressive strength and 28d flexural strength of the repair self-compacting polymer concrete obtained in Examples 8 to 9 are higher than those in Examples 7 and 10, indicating that the mass ratio of the first aggregate to the second aggregate is 3 to 4:1, which can further improve the compressive strength and flexural strength of the polymer concrete.

[0049] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A self-compacting polymer concrete for repair, characterized in that: It includes the following components in parts by mass: 15-35 parts of cement, 10-20 parts of porous sintered sand, 10-20 parts of quartz sand, 5-10 parts of gypsum, 25-35 parts of aggregate, 0.2-1.5 parts of wood fiber, 0.5-3 parts of water-retaining polymer, 1-3 parts of expansion agent, 0.3-1 parts of water-reducing agent, and 0.05-0.3 parts of early strength agent.

2. A self-compacting polymer concrete for repair according to claim 1, characterized in that: The mass ratio of the porous sintered sand to the wood fiber is 20:

1.

3. A self-compacting polymer concrete for repair according to claim 2, characterized in that: The aggregate comprises a first aggregate and a second aggregate in a mass ratio of 1:10 to 10:1, the first aggregate is an unmodified aggregate, and the second aggregate is an aggregate modified by a compound containing a naphthalene ring and a carboxyl group.

4. A self-compacting polymer concrete for repair according to claim 3, characterized in that: The mass ratio of the first aggregate to the second aggregate is 3-4:

1.

5. The self-compacting polymer concrete for repair according to claim 4, characterized in that: The raw materials of the second aggregate include a compound containing a naphthalene ring and a carboxyl group and an aggregate in a mass ratio of 1 to 5:

50.

6. The self-compacting polymer concrete for repair according to claim 5, characterized in that: The preparation method of the second aggregate comprises the following steps: dissolving a compound containing a naphthalene ring and a carboxyl group in a solvent, adding the compound into the aggregate and mixing the mixture evenly, and drying the mixture to obtain the second aggregate.

7. The self-compacting polymer concrete for repair according to claim 1, characterized in that: The gypsum includes one or both of anhydrous gypsum and hemihydrate gypsum.

8. The self-compacting polymer concrete for repair according to claim 1, characterized in that: The aggregate includes one or two of limestone crushed stones and pebbles.

9. The self-compacting polymer concrete for repair according to claim 1, characterized in that: The water-retaining polymer includes one or two of polyvinyl alcohol and sodium polyacrylate; the early strength agent includes one or two of triethanolamine and diethanolamine.

10. The method for preparing the self-compacting polymer concrete for repair according to any one of claims 1 to 9, characterized in that: The components in the above-mentioned parts by mass are mixed evenly to obtain a self-compacting polymer concrete for repair.